1999
DOI: 10.1002/(sici)1096-9896(199909)189:1<60::aid-path387>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein expression and nuclear size in benign, borderline, and malignant serous ovarian tumours

Abstract: Metallothioneins (MTs) are low‐molecular‐weight proteins involved in metalloregulatory functions such as cell proliferation, growth, and differentiation. In recent years, MT expression has been linked with carcinogenesis, resistance to cancer therapy, and tumour progression. However, the significance of MT expression in ovarian cancers is at present inadequately documented. In this study, MT immunohistochemistry was performed in 12 benign, 14 borderline, and eight malignant serous tumours of the ovary. The int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
6
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 29 publications
3
6
0
Order By: Relevance
“…In this study MT expression was found to be much more common in malignant than benign ovarian neoplasms of surface epithelial origin. This is in keeping with the findings in two previous studies investigating MT expression in benign, borderline, and malignant serous and mucinous ovarian neoplasms (21,22) . This suggests that increased MT expression accompanies malignant transformation in ovarian surface epithelial neoplasms.…”
Section: Discussionsupporting
confidence: 92%
“…In this study MT expression was found to be much more common in malignant than benign ovarian neoplasms of surface epithelial origin. This is in keeping with the findings in two previous studies investigating MT expression in benign, borderline, and malignant serous and mucinous ovarian neoplasms (21,22) . This suggests that increased MT expression accompanies malignant transformation in ovarian surface epithelial neoplasms.…”
Section: Discussionsupporting
confidence: 92%
“…Our results revealed the co-existence of at least two populations of cancer cells, a pan-cytokeratin high, SPARC negative population and a pan-cytokeratin low and SPARC positive population within the same tumor ( Figures 5F, S5B and Supplementary Video). In addition, pan-cytokeratin negative and SPARC high cancer cells could also be identified by their abnormal nuclei ( Figures 5G and S5C), which were distinct from the SPARC high fibroblasts cells (Tan et al, 1999). Similarly, this SPARC positive, pan-cytokeratin negative and mesenchymal-like subpopulation was observed in the KURAMOCHI cell line, which is known to faithfully represent HGSOC (Domcke et al, 2013).…”
Section: Emt-high Subtype Is Robustly Correlated With Poor Prognosismentioning
confidence: 77%
“…In recent years, metallothionein expression has been linked with carcinogenesis, resistance to cancer treatment and tumour progression. [5][6][7] Immunohistochemically detected metallothionein is not usually found in normal tissues, except in myoepithelial cells of the breast and epithelial cells of the kidney and thyroid. 4 Overexpression of metallothionein occurs frequently in human malignant tumours, but the underlying mechanism is unknown.…”
mentioning
confidence: 99%